Incorporating Discourse in Secondary Mathematics (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
During my teaching experience, I often came across students who could not speak about the mathematics that we were dealing with and had a disconnect between mathematical concepts and processes. I kept wondering, what do math educators and researchers know about discourse and how do we effectively engage students in it? When the teacher acts as a guide and uses certain strategies such as reflective discourse, funneling, or word walls, students will better conceptually understand the mathematics they are trying to learn. Not only will their conceptual understanding and achievement increase, but students will reap the important benefit of seeing math as created by communities. Learning about and implementing discourse is important for new and experienced teachers.